Dynamic Modelling of Axle Tramp in a Sport Type Car - Ali Zargartalebi; Kourosh Heidari Shirazi (Shock and Vibration)
One of the most significant dynamic aspects of coupled vibration of transmission system and dependent type suspension systems is axle tramp. The tramp is defined as undesirable oscillation of rigid live axle around roll axis. In spite of utilizing powerful engines in some type of sport cars, tramp occurrence causes loss of longitudinal performance. The aim of this paper is to derive a mathematical model for predicting and classifying of the tramp. A parameter study reveals that, some parameters such as engine torque, moving parts moment of inertia, car and wheels weight and the material used in suspension system play important role in controlling the tramp. It is shown that large difference between sprung and unsprung mass moment of inertia around the roll-axis, low vehicle mass, short rear track and medium damping values have significant effects on the severity of tramp.